Simulation analysis on CIGS solar cell on different absorber layer thickness subject to temperature change using SCAPS 1-D software - Harif M.N.; Abdullah S.F.; Mahmood Zuhdi A.W.; Za'Abar F.; Bahrudin M.S.; Hasani A.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
C (programming language); Computer software; Copper compounds; Efficiency; Energy gap; Gallium compounds; Indium compounds; Layered semiconductors; Open circuit voltage; Short circuit currents; Solar absorbers; Solar cells; Band gap energy; CIGS solar cells; Fill factor; SCAPS 1-D; Temperature coefficient; Temperature